Manifestations of Age on Autophagy, Mitophagy and Lysosomes in Skeletal Muscle - Matthew Triolo; David A. Hood (Cells, 2021)
Sarcopenia is the loss of both muscle mass and function with age. Although the molecular underpinnings of sarcopenia are not fully understood, numerous pathways are implicated, including autophagy, in which defective cargo is selectively identified and degraded at the lysosome. The specific tagging and degradation of mitochondria is termed mitophagy, a process important for the maintenance of an organelle pool that functions efficiently in energy production and with relatively low reactive oxygen species production. Emerging data, yet insufficient, have implicated various steps in this pathway as potential contributors to the aging muscle atrophy phenotype. Included in this is the lysosome, the end-stage organelle possessing a host of proteolytic and degradative enzymes, and a function devoted to the hydrolysis and breakdown of defective molecular complexes and organelles. This review provides a summary of our current understanding of how the autophagy-lysosome system is regulated in aging muscle, highlighting specific areas where knowledge gaps exist. Characterization of the autophagy pathway with a particular focus on the lysosome will undoubtedly pave the way for the development of novel therapeutic strategies to combat age-related muscle loss.